The Effectiveness of the Predict-Observe-Explain (POE) Model in The Physics Electronic Modules to Improve Critical Thinking Skills - Honesty Hidayah Nur Permatasari; Suharno; Risa Suryana (Jurnal Penelitian Pendidikan IPA, 2023)
A module is a learning media that is arranged systematically so that it is easy for students to use when receiving material taught by the teacher. Learning in schools using information technology is still not optimal, so it is necessary to develop electronic modules. Moreover, Indonesian students have low critical thinking skills. This study aims to create electronic modules that effectively improve students’ critical thinking skills. The method applied is Research and Development. The effectiveness of the developed electronic module can be determined by carrying out the N-gain test, which is obtained from evaluating students’ skills before and after using the generated module. The Kolmogorov-Smirnov normality test shows a significance score of 0.000 on the pre-test and post-test, which means that it is not normally distributed, so it is continued with the Wilcoxon test. The Asymp.Sig (2-tailed) of the Wilcoxon test is 0.000, meaning there is a difference between the scores before and after implementing the developed module. The average score of N-gain in the critical thinking skill variable is classified as a high category, namely 0.73. Conclusions are drawn regarding using the Predict-Observe-Explain (POE) model in electronic modules that can improve critical thinking skills, proven effective in learning physics.